Law, responsibility, and vulnerability state accountability and responsiveness - Gallen, James; Ní Mhuirthile, Tanya (Milton Park, Abingdon, Oxon [UK] ; New York, NY : Routledge, 2021)
This book addresses how law and public policy cause or exacerbate vulnerability in individuals and groups. Bringing together scholars, judges and practitioners, it identifies how individuals and groups can become vulnerabilised through the operation of law, and examines how the State can acknowledge and remedy that impact. The book offers not only a theoretical, ethical and normative conception of vulnerability in law, but also an evaluation of the diverse practices of responding to vulnerability in law through accountability mechanisms and public campaigns. The analysis of vulnerability contained in this volume is enhanced by the common use of Ireland as a case study. Despite the robust rights protections available at national, regional and international level, Ireland remains a State where at risk people have experienced vulnerability across a range of thematic areas, such as criminal law, migration and asylum, historical abuse, LGBTI rights and austerity. Drawing on comparative analyses and a consideration of the role of international law in domestic settings, this book offers a comparison of diverse national and transnational attempts to ensure State accountability and responsiveness to legally created vulnerabilities. The book demonstrates lessons learned from theory and practice regarding how vulnerability can be experienced by individuals and groups, structured by law and addressed through legal and political action. This book will be of considerable interest to socio-legal and "law and society" scholars, as well as others working in international human rights, jurisprudence, philosophy, legal theory, political theory, feminist theory, and ethics.
Keywords: Public policy (Law) -- Ireland; Law -- Ireland; Government liability -- Ireland; International and municipal law -- Ireland; Vulnerability (Personality trait) -- Social aspects; LAW / General; LAW / Gender & the Law; LAW / Discrimination